Role of AI in Educational Sector With Reference to Tirupur - Karpagavalli, V.; Poornima, G.; Arthi, M.; Sathya, M. (Indian Journal of Computer Science, 2024)
Artificial Intelligence (AI) is increasingly being integrated into various facets of education, revolutionizing traditional learning environments. This journal explores the role of AI in education, particularly focusing on its impact in Tirupur City, a key industrial hub in Tamil Nadu, India. The study examines how AI tools and technologies are being utilized to enhance teaching methodologies, streamline administrative processes, and personalize student learning experiences. The analysis is contextualized through existing research in AI's role in remote learning, with reference to the specific challenges and opportunities in Tirupur.